Violence, terrorism, and justice - Frey, R.G. (Raymond Gillespie); Morris, Christopher W. (Cambridge studies in philosophy and public policy, 1991)
The essays in this volume by a group of moral and social thinkers define terrorism, discuss whether the assessment of terrorist violence should be based on its consequences (beneficial or otherwise), and explore what means may be used to combat those who use violence without justification.